2022
DOI: 10.25115/ejrep.v20i58.6328
|View full text |Cite
|
Sign up to set email alerts
|

<p>Promoting Communication for Young Children with Autism Spectrum Disorders: A Family-centered Music Therapy Intervention</p>

Abstract: Introduction.  Autism Spectrum Disorders (ASD) are a continuum of traits that may negatively affect social and emotional competencies of individuals, including challenges in their engagement abilities, possible limitations in reciprocal interactions, and inflexibility in initiating and sustaining communication. Such challenges may affect language development and speech acquisition. Considering their importance, this study explored the impact of a family-centered, music therapy intervention to promote preverbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These results seem to confirm the results of other experimental and case studies [16,21,23,24,[44][45][46]. In particular, Kim et al (2009) [16] found a positive relationship between music therapy and the child's emotional synchronization with the therapist.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These results seem to confirm the results of other experimental and case studies [16,21,23,24,[44][45][46]. In particular, Kim et al (2009) [16] found a positive relationship between music therapy and the child's emotional synchronization with the therapist.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in two of the studies, there was an increase in children's imitative ability, comprehension, and interaction maintenance [13,41]. The effect of family-centered music therapy (FCMT) on socioemotional functioning and the development of social interaction of children with ASD in different social contexts and their interaction with parents also seems to be positive [31,42]. Another important factor is the level of language.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations